Physiological significance of antithrombin D-helix interaction with vascular GAGs - Biswas, Indranil; Panicker, Sumith R.; Lupu, Florea; Rezaie, Alireza R. (Blood advances, 2025)
•Interaction of D-helix of AT with therapeutic heparins promotes the protease-inhibitory function of the serpin.•Interaction of D-helix of AT with vascular GAGs unveils the anti-inflammatory signaling function of the serpin. [Display omitted] Antithrombin (AT) is an anticoagulant serpin involved in the regulation of proteolytic activities of coagulation proteases. AT also possesses a direct anti-inflammatory function. The anticoagulant function of AT is mediated through its reactive center loop–dependent inhibition of coagulation proteases, but anti-inflammatory function of AT is mediated via its D-helix–dependent interaction with vascular glycosaminoglycans (GAGs). In vitro assays have established that therapeutic heparins promote the anticoagulant function of AT by binding D-helix and activating the serpin, however, the contribution of vascular GAGs to D-helix–dependent anticoagulant function of AT has remained poorly understood in vivo. Here, we explored this question by using 2 AT mutants, (AT-4Mut), which exhibits neither affinity for heparin nor D-helix–dependent anti-inflammatory signaling but possesses normal protease-inhibitory function and an inactive signaling-selective AT mutant in which its P1-Arg425 is deleted (AT-R425del). In vivo properties of mutants were compared with wild-type AT (AT-WT) in a small interfering RNA (siRNA)-mediated AT-deficient mouse model. The siRNA knockdown efficiently reduced expression of AT and induced robust procoagulant and proinflammatory phenotypes in mice. Infusion of both AT-WT and AT-4Mut rescued the procoagulant phenotype of AT-deficient mice as evidenced by restoration of the plasma clotting time and inhibition of fibrin deposition. AT-WT also attenuated inflammation as evidenced by reduced VCAM-1 expression and leukocyte infiltration in the liver and lungs; however, AT-4Mut failed to attenuate inflammation. Interestingly, AT-R425del also effectively attenuated inflammation in AT-depleted mice. These results suggest that interaction of AT D-helix with vascular GAGs may primarily be responsible for anti-inflammatory signaling rather than protease-inhibitory function of the serpin.